Penggunaan Kapur Padam Sebagai Pengganti Filler Pada Campuran AC-WC - Hendra Cahyadi; Sucmana Wijaya Kasuma (Media Ilmiah Teknik Sipil, 2018)
Asphalt Concrete-Wearing Course (AC-WC) has been used widely in Indonesia as a surface layer, because of its water-resistant nature and high durability. An essential characteristic of Asphalt Concrete is that its continuous graded aggregate produces a pavement layer with high stability properties. Fillers as fillers in asphalt mixes. In this study, lime was used as a substitute for fillers in the AC-WC mixture. Extinguished lime is a material that passes the no. 200 (0.075 mm), as the primary condition for filler material. The purpose of this study was to determine the Marshall characteristics of the AC-WC mixture using extinguished lime fillers and to assess the performance of the mix and the effect of quenched lime fillers in the AC-WC mixture. The research method was carried out in several stages starting from inspection of 60/70 asphalt penetration, abrasion testing (Los Angeles), screening analysis, aggregate specific gravity testing, Sand Equivalent testing, testing of concrete mixture particular gravity up to testing with Marshall tools. From the results of the study, the use of extinguished filler lime in the AC-WC mixture showed that the use of quenched lime as a filler substitute fulfilled the requirements of stability, flow, VFB, VMA and Marshall Results.